Associations of epidemiologic risk factors with Fusobacterium nucleatum and bacterial alpha diversity in the colorectal tumor-associated microbiota - Hill CM; Malen RC; Reedy AM; Kahsai O; Curtis K; Ma N; Randolph TW; Ma J; Thomas CE; Ogino S; Potter JD; Buchanan DD; et al. (Springer Nature, 2026)
Background Aspects of the gut microbiome, including presence of specific bacterial species and overall community structure, have been linked to the etiology and prognosis of colorectal cancer (CRC). Less is known about the epidemiologic risk factors that are associated with the composition of the microbiota in invasive colorectal tumors. Methods Using tumor and paired normal colorectal tissue samples from a subset of participants in the population-based Seattle Colon Cancer Family Registry, we compared the presence of Fusobacterium nucleatum (F. nucleatum) (n = 898) measured via droplet digital PCR and alpha diversity (Shannon index) (n = 611) measured via 16S rRNA gene sequencing in colorectal tissue across demographics, health behaviors, and neighborhood socioeconomic status (nSES). Results Normalized counts of F. nucleatum were consistently higher in tumor tissue than in patient-matched normal tissue across all risk factors, while alpha diversity was lower. Female sex was associated with high presence and enrichment of F. nucleatum in tumor tissue (odds ratio [OR] 1.61; 95% confidence interval [CI] 1.02, 2.54 and OR 1.58, 95% CI 1.10, 2.27, respectively). Relative to those aged 40–49 years, the youngest age group (< 40 years) had lower alpha diversity in tumor tissue (OR for highest vs. lowest tertile: 0.33; 95% 0.13, 0.83). Other factors, including diet, were not related to F. nucleatum presence or tumor tissue alpha diversity. Conclusion By uncovering epidemiologic risk factors for F. nucleatum presence and bacterial diversity in the intratumoral microbiota, this work informs our understanding of associations of the gut microbiota with CRC etiology and outcomes.
Keywords: Intratumoral microbiome; Fusobacterium; 16S rRNA gene sequencing; Bacterial diversity; CRC; SCCFR; Diet; Physical activity; Socioeconomic status; ddPCR